Application of Quantum Dot Down-Conversion Layer in Thin-Film Solar Cells to Increase Short-Wavelength Spectral Response. (20th May 2021) - Yu, Jong Hun; Cho, Dae-Hyung; Lee, Woo-Jung; Kim, Woo-Ju; Kang, Seong Jun; Chung, Yong-Duck
Abstract : The short-wavelength optical loss in the Cu(In, Ga)Se2 (CIGS) thin-film solar cells is inevitable owing to the substantial light absorption in the front layers such as the buffer layer and transparent conducting oxide (TCO) layer. Quantum dots (QDs) with CdSe/ZnS core–shell structure is utilized to increase the short-wavelength spectral response of the CIGS thin-film solar cells. The QDs absorbs photons in the short-wavelength region (<540 nm) and re-emits the photons at approximately 540 nm; these photons penetrate the front layers and reach the CIGS absorber layer. The thickness of the QD layer was varied via drop coating with different QD concentrations, thereby facilitating the application of the optimized QD layer as a down-conversion layer in the CIGS thin-film solar cells. The photoelectric parameters of the CIGS thin-film solar cells were dependent on the QD thickness, and they were characterized using quantum efficiency measurements, spectrophotometric analysis, and current–voltage measurements. The CIGS thin-film solar cells with a 0.7 μ m-thick QD layer exhibited the highest increase of 1.86 mA cm −2 and 0.75% in the short-circuit current density and efficiency, respectively.